Line positions, pressure broadening and shift coefficients for the second overtone transitions of carbon monoxide in argon. (April 2017) - Kowzan, G.; Stec, K.; Zaborowski, M.; Wójtewicz, S.; Cygan, A.; Lisak, D.; Masłowski, P.; Trawiński, R.S.
Abstract: Absolute positions and spectral line-shape parameters of carbon monoxide 0 → 3 band, P branch transitions are reported. The speed-dependent effects and the influence of velocity-changing collisions were taken into account in the fitted line-shape models. For the first time the values of pressure shift coefficients of CO in argon for this band were determined. The measurements were made with the Pound–Drever–Hall-locked frequency-stabilized cavity ring-down spectrometer, with the frequency axis linked through an optical frequency comb to the UTC(AOS) frequency reference based on a hydrogen maser. Achieved uncertainties of line positions are between 70 kHz and 420 kHz. Abstract : Highlights: Five P branch 3–0 band transitions of carbon monoxide in argon were measured. Line positions were determined with accuracy better than 420 kHz. Frequencies were linked to primary frequency standard through UTC(AOS) reference. First line shift measurements of CO 3–0 band in argon were done.